Sixth Periodic Monitoring Report on the Status of Implementation Plans in Response to Board-Endorsed IEO Recommendations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
IMF staff and completed on June 30, 2014 for the Executive Board's consideration on August 7, 2014.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet